Microstructure and Wear Behavior of Al2218-B4C Nano Composites - Vidyadhar Pujar, Srinivas H K, Sahadeva G N, Mamunuri Sailender, Madeva Nagaral (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The effect of nano B4C particle addition on the wear behaviour of Al2218 alloy composites has been investigated. Al2218 combination with 2 to 8 wt. % of nano B4C composites were manufactured by stir technique. Microstructural study was completed by utilizing SEM and EDS. A pin-on-disc machine was used to evaluate the wear loss of examples, in which a set EN32 steel plate was used as the counter face. Wear tests were went with on Al2218 compound with nano B4C particles strengthened composites at different loads of 9.8 N, 19.6 N, 29.4 N and 39.2 N with steady sliding rate of 2.8 m/sec and 2000 m sliding separation. Also, Wear tests were went with on Al2218 amalgam with nano B4C particles strengthened composites at different paces of 1.4 m/sec, 1.8 m/sec, 2.3 m/sec and 2.8 m/sec with consistent load of 39.2 N and 2000 m sliding separation. The wear opposition of Al2218 compound improved with the gathering of B4C particulates. Further, worn surface morphology and wear debris of prepared composites were studied to know the different wear phenomena.